2018
DOI: 10.1111/bjd.16335
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hyaluronan and increased expression of HYBID (alias CEMIP and KIAA1199) correlate with clinical symptoms in photoaged skin

Abstract: These data demonstrate that imbalance between HYBID-mediated HA degradation and HAS-mediated HA synthesis may contribute to enhanced HA catabolism in photoaged skin, and suggest that HYBID-mediated HA reduction in the papillary dermis is related to skin wrinkling and sagging of photoaged skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 39 publications
9
50
0
3
Order By: Relevance
“…Facial wrinkling rate over the years is also known to linearly increase in French, but not Chinese women, and wrinkle onset is delayed by about 10 years in Chinese women as compared with French women . In our parallel study on the Japanese women, we examined the relationship of HA level and HYBID expression with photodamaged skin wrinkling and sagging by comparing the photoprotected and photoexposed skin samples from the same donors, and obtained the similar findings to the present study: The reduced level of HA and overexpressed HYBID in the superficial dermis directly correlate with skin roughness and sagging parameters in the crow's‐foot area . Since the age distributions of the Caucasian women (age range, 60‐69 years; mean age, 62.2 years) in the present study and the Japanese women (age range, 65‐72 years; mean age, 69.1 years) in the parallel study are not significantly different, the data suggest that HYBID‐mediated HA reduction in the superficial dermis of the skin at the photoaged eye corner could be a common basis underlying wrinkle formation in both Caucasian and Japanese women aged over 60 years.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Facial wrinkling rate over the years is also known to linearly increase in French, but not Chinese women, and wrinkle onset is delayed by about 10 years in Chinese women as compared with French women . In our parallel study on the Japanese women, we examined the relationship of HA level and HYBID expression with photodamaged skin wrinkling and sagging by comparing the photoprotected and photoexposed skin samples from the same donors, and obtained the similar findings to the present study: The reduced level of HA and overexpressed HYBID in the superficial dermis directly correlate with skin roughness and sagging parameters in the crow's‐foot area . Since the age distributions of the Caucasian women (age range, 60‐69 years; mean age, 62.2 years) in the present study and the Japanese women (age range, 65‐72 years; mean age, 69.1 years) in the parallel study are not significantly different, the data suggest that HYBID‐mediated HA reduction in the superficial dermis of the skin at the photoaged eye corner could be a common basis underlying wrinkle formation in both Caucasian and Japanese women aged over 60 years.…”
Section: Discussionsupporting
confidence: 79%
“…We have recently reported that HYBID (HYaluronan Binding protein Involved in hyaluronan Depolymerization, KIAA1199) plays an essential role in HA degradation in human normal skin fibroblasts . Our recent study also demonstrated that in the Japanese women, HYBID is overexpressed in the photoexposed skin compared with the photoprotected skin and up‐regulation of HYBID is correlated with HA reduction in the papillary dermis of the photoexposed skin, showing positive correlations with skin wrinkling and sagging . Since skin wrinkling is well known to ethnically differ between Caucasian and Japanese women, roles of HA and its metabolism in wrinkle formation may be different between both of the races.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our recent study also demonstrated that quantity and molecular size of HA are decreased in the photoaged skin compared to the photoprotected skin accompanying increased expression of HYBID and decreased expression of HAS1/2 in the Japanese women. In addition, expression levels of HYBID , but not HAS1/2 , are directly correlated with reduction of HA in the papillary dermis of the photoaged skin, showing positive correlations with skin wrinkling . We also reported similar results on the photoaged skin in the Caucasian women: the expression levels of HYBID positively correlated with skin wrinkling at the outer eye corner, and HA in the papillary dermis was significantly lower in skin with high‐HYBID‐expression than in skin with low‐HYBID expression .…”
Section: Introductionsupporting
confidence: 72%
“…Wrinkle formation, a representative symptom of photoaging, is characterized by decreased skin elasticity and deterioration of extracellular matrix components of the dermis, which are mainly composed of collagen fibers, elastic fibers, and hyaluronan (HA) . Although previous studies suggested that damaged and disorganized collagen fibers and massive accumulation of abnormal elastic material in the reticular dermis are associated with skin wrinkle formation, we have recently demonstrated that reduction of HA in the papillary dermis and overexpression of HYBID (HYaluronan Binding protein Involved in hyaluronan Depolymerization, alias KIAA1199, or CEMIP), a key molecule for HA degradation in normal human skin fibroblasts, are related to facial skin wrinkling …”
Section: Introductionmentioning
confidence: 99%